Archiving ERP data to enhance operational effectiveness: the case of Dolphin. (2017) - Srivastava, Shalini; Misra, Richa
Transaction-intensive, customer facing applications and the most critical high volume ERP and CRM applications are collecting and storing huge amount of data resulting in exponential increase in the size of database. ERP applications are based on layered architecture and complicated relational databases. An overloaded relational database reduces ERP performances and increase hardware and maintenance cost. Managing security and growth of databases size has become the prime concern of organisation to enhance performance and reduce cost. The article has taken a case study to highlight why data archiving is crucial for the enterprises running SAP solution in optimising business performance. The present article discusses the challenges faced by an organisation in managing the growing SAP data and how a data management strategy in place can help the organisation in enhancing the performance of the system.